The Strategic Role of Engagement and Positive Workplace to Sustain Employee Performance - Pramesthi Widyasari, Septiningtyas; Fachrunnisa, Olivia (Journal of Public Administration and Governance, 2024)
Employee performance is an important factor for a company to achieve objectives, gain competitive advantage and finally winning the competition. Even for a company which has been established for more than 20 years, employee performance still becomes challenge. A good relationship between leader and member is one of the key factors to improve employee performance. A company needs to ensure that employees give their best performance and meet the expectation. The purpose of this study is to develop model to improve employee performance with high quality of Leader-Member Exchange (LMX) and Perceived Organizational Support (POS) which mediates by work engagement. Data were collected from 100 respondents of permanent employees in a teak furniture manufacturing company in Semarang, Central Java Province, Indonesia. The method used to analyze the hypotheses was Partial Least Square (PLS). This study concludes that positive workplace which contains Leader-Member Exchange (LMX), Perceived Organizational Support (POS), and Work Engagement, have a positive and significant influences on Employee Performance. Work Engagement also found has influence effect on mediating between LMX and POS with Employee Performance.